Body mass index profile among school children: an anthropometric study - Mahalakshmi, S.; Abirami, M. J. (International Journal Of Community Medicine And Public Health, 2019)
Background: The study aimed to analyse the trends in the growth pattern of the children in the age group of 3-21 years of both boys and girls using body mass index (BMI). The study also compared the BMI of the sample with the WHO norms and the group average. Methods: A study was conducted in India covering 1728 children 849 boys and 879 girls from LKG grade to +2 grades in the age group of 3-21 years. BMI grades were computed as per WHO 2006 standards (underweight- <18.50, normal- 18.50-24.99, overweight- >25.00 and obese- >30.00). Results were analyzed using percentage and ANOVA. Results: The data shows that 88.9% of children in the age group of 3-8 years are underweight and in 15-21 years of age children are relatively healthy, but are inclined to move to overweight (17.66%) and obesity (7.21%). More of boys (31%) tend to be underweight than girls. Age and gender were found to be significantly related to BMI. The average BMI of the sample group is above the national standards of WHO (World Health Organization) in all the three age groups. Boys are found to be on par with WHO norms while girls exceed the same. Majority of the sample were below the average denoting underweight. Conclusions: Age and gender was significantly related with BMI. Average BMI of the sample was on par with national standard of WHO. BMI was thus found to be an effective tool for predicting the well-being of school children.